1976
DOI: 10.1073/pnas.73.7.2491
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibodies in sera from healthy humans to antigens on surfaces of type C RNA viruses and cells from primates.

Abstract: The gibbon lymphosarcoma cells releasing gibbon ape leukemia virus were used in a screening study of sera from healthy humans. Out of 72 sera screened by indirect immunoelectronmicroscopy using this system, 55 were positive (76%); i.e., 26 out of 35 males (74%) and 29 out of 37 females (78%). The highest incidence of antibody production was in 1-to 1O-year-olds and 31-to 40-year-olds, with the adults exhibiting higher levels. Differences in incidence of natural antibody were not found to be sex-linked. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…1,2,70,71 Additional studies could not confirm the previous findings, demonstrating that the observed seroreactivity to GaLV antigens was most likely nonspecific reactivity to cellular antigens contaminating the viral preparations or related antigens present in the fetal calf serum used for cell line maintenance. 59 In addition, testing using more sensitive PCR-based assays has not supported the serologic evidence of GaLV infection.…”
Section: Human Infection With Galvcontrasting
confidence: 47%
“…1,2,70,71 Additional studies could not confirm the previous findings, demonstrating that the observed seroreactivity to GaLV antigens was most likely nonspecific reactivity to cellular antigens contaminating the viral preparations or related antigens present in the fetal calf serum used for cell line maintenance. 59 In addition, testing using more sensitive PCR-based assays has not supported the serologic evidence of GaLV infection.…”
Section: Human Infection With Galvcontrasting
confidence: 47%
“…Radioimmunoassays may be expected to be more sensitive than the neutralization tests applied in this study. Antibodies to SSV antigens were also found using cells productively infected with the virus, and studied by an indirect immunoelectron microscopy assay (Aoki et al 1976 ). In contrast, radioimmunoassays with the purified proteins p3o and gp7 o of SSV did not detect precipitating antibodies in various groups of patients, including 35 cases of lupus erythematosus (Stephenson & Aaronson, 1976).…”
Section: Discussionmentioning
confidence: 93%
“…Again autoantibodies to retrovi ruses [37,38] or tumor antigens [39] are excluded from consideration. The classical autoimmune human diseases in which au toantibodies and immune complexes are known to play a key etiologic role [cf.…”
Section: Autoantibodies In Humans: Occurrence and Significancementioning
confidence: 99%